I assume your equation is
9n^3 * (1/(3n))^4 =
9n^3 / (3n)^4 =
9n^3 / 81n^4 =
1/9n
2007-01-25 05:42:36
·
answer #1
·
answered by catarthur 6
·
0⤊
2⤋
Start by operating on the term in () first:
(1/3n)**4 becomes 1/81n**4 or (n**-4)/81
Then multiply by the other term (multiply or divide coefficients, add or subtract exponents):
9n**3 times (n**-4)/81 becomes (n**-1)/9, or 1/9n
2007-01-25 13:45:09
·
answer #2
·
answered by W E 2
·
0⤊
1⤋
9n³(1/3n)^4 =
9n³(1/81n^4) =
(9 * 1/81)(n³.n^4) =
1/9 * n^7 = n^7 over 9
><
2007-01-25 13:43:29
·
answer #3
·
answered by aeiou 7
·
0⤊
0⤋
I think you are overthinking.
Take it slow.... start with (1/3n)^4
The numerator (top) will be 1^4, which is just 1.
The denominator (bottom) will be (3n)^4.
3^4 is 3x3x3x3 = 81
n^4 is simply written as n^4
These are multiplied, so the denominator is 81n^4
The term (1/3n)^4 then equals (1/81n^4) = top/bottom
Now multiply (9n^3)(1/81n^4)
Top number is (9n^3)(1) = 9n^3
Bottom is still 81n^4
Simplify the number part: (9/81) = 1/9
Simplify the variable part: (n^3/n^4) = (1/n)
These are multiplied together, so your final answer will be
(1/9n)
2007-01-25 13:46:05
·
answer #4
·
answered by MamaMia © 7
·
0⤊
1⤋
9n^3 (1/3n)^4
= 9n^3 (1/3)^4 n^4
= 9n^7 (1/81)
= n^7 / 9
2007-01-25 13:41:39
·
answer #5
·
answered by MsMath 7
·
1⤊
1⤋
9n^3(1/3n)^4
=9n^3 (1^4/(3n)^4)
= 9n^3*(1/81n^4)
= 9n^3/81^4
= 1/ 9n
2007-01-25 13:52:15
·
answer #6
·
answered by ironduke8159 7
·
0⤊
0⤋
9 is 3^2
3^2*n^3*3^(-4)*n^4
3^(-2)*n^7
(n^7)/9
2007-01-25 13:41:35
·
answer #7
·
answered by bequalming 5
·
1⤊
1⤋